Prenatal Diagnosis of Maternal-Fetal Blood Subgroup Antigen Incompatibility Due to C Antigen: A Case Report - Ebru Biberoğlu; Cihan Toğrul; Seval Özgü Erdinç; Ece Gül Tuncer; Dilek Uygur; Nuri Danışman (Medical Network, 2016)
In this paper, we report a case of materno-fetal C-subgroup incompatibility that was managed at our institution. A 41-year-old woman was admitted to our prenatal outpatient unit for the first time at 29th week of a singleton pregnancy. After an indirect coombs test result of 1/64 positive, cordocentesis was performed. Fetal blood group was reported as AB Rh(-), and Direct coombs test was reported to be +3 positive. A 3040 gr live fetus was delivered by cesarean section, on the 34th week of pregnancy. Maternal blood samples revealed C(-), c(4+), E(-), e (4+) and Kell (-), and the fetus had direct coombs 3+, C(4+), c(3+), E (-), e (4+) and Kell (-). No fetal complications occurred.